Bright burning things : a novel - Harding, Lisa (HarperVia, an imprint of HarperCollinsPublishers, 2021)
"Sonya used to perform on stage. She used to attend glamorous parties, date handsome men, ride in fast cars. But somewhere along the way, the stage lights Sonya lived for dimmed for good. And then, in their absence, came darkness--blackouts, empty cupboards, hazy nights she can't remember. Haunted by her failed career and unresolved childhood trauma, Sonya has fallen deep into an alcoholic abyss. What keeps Sonya from losing herself completely is Tommy, her son. But her love for Tommy is in fierce conflict with her love of the bottle. Addiction preys on her fear of losing Tommy, as every maternal misstep compels her to drink. But soon, Sonya will be forced to make a choice. Give up drinking or lose Tommy--forever. Bright Burning Things is an emotional tour-de-force, offering a devastating and nuanced look at an addict's journey towards rehabilitation and redemption"--